Respostas

A melhor resposta!
2014-08-11T22:48:26-03:00
Olá, Gabrielfut10!

a) y² - 7y + 12 = 0
a = 1
b = -7
c = 12

Δ = b² - 4ac
Δ = (-7)² - 4.1.12
Δ = 49 - 48
Δ = 1

-b +- √Δ / 2.a
-(-7) +- √1 / 2.1
7 +- 1 / 2

x' = 7+1/2 = 8/2 = 4
x'' = 7-1/2 = 6/2 = 3

S = {4,3}

b) x² + 6x + 8 = 0
a = 1
b = 6
c = 8

Δ = b² - 4ac
Δ = 6² - 4.1.8
Δ = 36 - 32
Δ = 4

-b +- √Δ / 2.a
-6 +- √4 / 2.1
-6 +- 2 / 2

x' = -6+2/2 = -4/2 = -2
x'' = -6-2/2 = -8/2 = -4

S = {-2, -4}
2 5 2
2014-08-11T22:55:57-03:00
A) y²-7y+12=0

Δ=b²-4*a*c
Δ=(-7)²-4*1*12=
Δ=49-48
Δ=1
√Δ=1

                      y=-b+-√Δ                    
                             2a
                     y=-(-7)+-1 
                            2*1

y'=  7+1                    y"=  7-1   
       2                                 2
y'= 8/2                      y"= 6/2
y'=4                          y"= 3

b) x²+6x+8=0

Δ=6²-4*1*8
Δ= 36-32
Δ= 4
√Δ= 2

          x=  -6+-2 
                  2

x'=  -6+2               x"=  -6-2   
        2                            2
x'= -4/2                 x"= -8/2
x'=-2                     x"= 4
1 5 1